2018
DOI: 10.2139/ssrn.3122342
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity after Commitment Lotteries: Examining Long-Term Results in a Cluster Randomized Trial

Abstract: General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.-Users may download and print one copy of any publication from the public portal for the purpose of private study or research -You may not further distribute the material or use it for any profit-making activity or commercia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Participants in the lottery arm receive the same treatment as the control arm in all aspects and additionally participate in lotteries. Prize sizes were chosen such that the weekly expenses per participant in proportion to the Dutch minimum wage were similar (0.6%) to a previous effective instance of this lottery [31]. We also mimic the lottery-deadline schedule in the best performing trialarm to promote gym attendance in Van der Swaluw et al [31].…”
Section: Intervention Arm: Smoke-free Lottery Weeks 1 To 13mentioning
confidence: 99%
See 1 more Smart Citation
“…Participants in the lottery arm receive the same treatment as the control arm in all aspects and additionally participate in lotteries. Prize sizes were chosen such that the weekly expenses per participant in proportion to the Dutch minimum wage were similar (0.6%) to a previous effective instance of this lottery [31]. We also mimic the lottery-deadline schedule in the best performing trialarm to promote gym attendance in Van der Swaluw et al [31].…”
Section: Intervention Arm: Smoke-free Lottery Weeks 1 To 13mentioning
confidence: 99%
“…A promising design used by behavioral economists and medical professionals is the use of regret lotteries, which have been demonstrated to support weight loss [27], medication adherence [28] and physical activity [29,30] at relatively low costs [31] across differing populations [32]. By their design, the lotteries aim to tap into multiple psychological insights on decision-making, with the goal to gain as much health out of every euro spent.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the app included the lottery-based incentives custom to this study (i.e., details can be read in the next section). Prior studies that have evaluated the impact of lotterybased incentives have hosted and communicated their incentives outside the digital tool that supported their intervention (e.g., by sharing lottery outcomes via e-mail, or text messages) (18,20). To provide a more integrated experience, we hosted the lotterybased incentives inside the our app (i.e., as is common in presentday entertainment games).…”
Section: Intervention Contextmentioning
confidence: 99%
“…Additionally, a study by Van der Swaluw and colleagues found that lottery-based incentives can increase physical activity levels and gym attendance in overweight adults (18). Particularly, in that study, regret lotteries were found to have a profound impact on participant engagement levels (18). In a regret lottery, prizes are drawn from all participants.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation